Tryptophan Catabolism and Inflammation: A Novel Therapeutic Target For Aortic Diseases - Ramprasath, Tharmarajan; Han, Young-Min; Zhang, Donghong; Yu, Chang-Jiang; Zou, Ming-Hui (Frontiers in Immunology, 2021)
Aortic diseases are the primary public health concern. As asymptomatic diseases, abdominal aortic aneurysm (AAA) and atherosclerosis are associated with high morbidity and mortality. The inflammatory process constitutes an essential part of a pathogenic cascade of aortic diseases, including atherosclerosis and aortic aneurysms. Inflammation on various vascular beds, including endothelium, smooth muscle cell proliferation and migration, and inflammatory cell infiltration (monocytes, macrophages, neutrophils, etc.), play critical roles in the initiation and progression of aortic diseases. The tryptophan (Trp) metabolism or kynurenine pathway (KP) is the primary way of degrading Trp in most mammalian cells, disturbed by cytokines under various stress. KP generates several bioactive catabolites, such as kynurenine (Kyn), kynurenic acid (KA), 3-hydroxykynurenine (3-HK), etc. Depends on the cell types, these metabolites can elicit both hyper- and anti-inflammatory effects. Accumulating evidence obtained from various animal disease models indicates that KP contributes to the inflammatory process during the development of vascular disease, notably atherosclerosis and aneurysm development. This review outlines current insights into how perturbed Trp metabolism instigates aortic inflammation and aortic disease phenotypes. We also briefly highlight how targeting Trp metabolic pathways should be considered for treating aortic diseases.